Дослідження українського козацтва у науковому спадку Д. Я. Телегіна (за документами з Наукового архіву ІА НАН України) - Станиціна, Г.О. (Археологія і давня історія України, 2020)
У публікації розглянуто документи з особового
фонду видатного вченого, Дмитра Яковича Телегіна, що зберігаються в НА НАН України та стосуються дослідження українського козацтва. The Scientific Archive of the Institute of Archaeology
of the National Academy of Sciences of Ukraine keeps
the personal holding of the prominent Ukrainian archaeologist
Dmytro Telehin (1919—2011), Doctor of historical
sciences, Professor, who studied archeological sites from
the Paleolithic to the Middle Ages. The entire home archive
of the scholar whose materials are arranged according
to the archeological periods was brought to the Scientific
Archive. Within the thematic complex the documents
are arranged by dates and content.
This publication is devoted to those documents of the
personal fund D. Ya. Telehin, which relate to the study of
archaeological sites and history of the Ukrainian Cossacks.
TThe collection contains: field diary, copies of scientific reports
on archeological excavations, drawings and plans of
the area and excavations, photographs and drawings of
finds and other documents. Archival materials related to
the study of the Sich territories where the Cossacks lived
and their necropolises are located, were dated from 1990
to 1994. Dmytro Telehin inspected and researched the following
Cossack Sichs: Tomakivska (1564—1593) near the
town of Marhanets; Bazavlutska (1593—1630) near the
village of Leninske; Mykytynska (1638—1652) in Nikopol;
Chortomlytska or as it was also called Kapulivska, or «old»
(1652—1709) near the village of Kapulivka; Pokrovska,
which was called «new» (1734—1775), near the village of
Pokrovsk in the Kherson region.
The personal stock of D. Ya. Telehin contains the documents
that reflect the visit of the scholar to island of
Khortytsia, the research of the Oleshkivska Sich (1711—
1728), as well as the camp of Severyn Nalyvaiko on
Turkachivsky hill near the village of Solonitsa (in 1596),
Poltava region. Of considerable interest are the documents
about the journey of D.Ya. Telegin to the island of
Solovky, Arkhangelsk region where Petro Kalnyshevsky,
the last Hetman of the New Sich, has been exiled.
The scholar’s collection also contains his lifetime
publications on the topic of the Cossacks, the layout of
the book «Cossack times. Sich Zaporiz`ka» and other
documents concerning Ukrainian Cossacks, their places
of residence and burial.